Pengaruh Penggunaan Media Pembelajaran Berbasis ICT (Information Communication Technology) Terhadap Hasil Belajar Ekonomi Siswa Kelas X Adm SMK Swasta Panca Dharma Kota Padangsidimpuan - Surayya, Laila; Vebrina, Dinda; Harahap, Fitriani; lbs, Aminah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the effect of using ICT (Information Communication Technology)-based learning media on the economic learning outcomes of Grade X ADM students at SMK Swasta Panca Dharma, Padangsidimpuan City. The method used is a quantitative approach with a descriptive quantitative method involving all 30 students of Grade X ADM as the total sample. Data were collected through a closed questionnaire based on a Likert scale to measure the use of learning media and documentation of the odd semester The data analysis technique used is the t-test. The descriptive analysis results show that the average use of ICT-based learning media falls into the 'Good' category with an average score of 75.67, while the students' learning outcomes in economics also fall into the 'Good' category with an average score of 75.23. The hypothesis test using the t-test shows a calculated t-value of 5.879, which is greater than the table t-value of 1.699 and the significance value of 0.001 < 0.05, indicating a significant effect of ICT-based learning media usage on students' learning outcomes in economics. It can be concluded that the use of ICT-based learning media has been proven to positively contribute to improving the learning outcomes in economics for students at Panca Dharma Private Vocational School in Padangsidimpuan.